76Causes, safety and outcomes of switching from the Initial direct oral anticoagulant to another in patients with non-valvular atrial fibrillation from a single-center prospective study. (18th June 2020) - Marchetti, G; Bernardini, F; Della Riva, D; Gambetti, S; Grazi, P; Lauria, G; Passarelli, P; Romoli, M; Zaniboni, A; Urbinati, S
Abstract: Background: Crossover between direct oral anticoagulants (DOACs) in real-life setting has been under investigated, with electronic registry-based study missing minor bleedings and minor ischemic events. The purpose of this study was to evaluate the switch from a DOAC to another DOAC, the reasons and the clinical events which happened after the switch. Methods Patients (pts) receiving first DOAC prescription at the Anticoagulation Center from February 2018 to September 2019 were consecutively included and followed. Causes of switch/dosage change as well as events or adverse events not leading to switch were registered. Results Overall, 300 pts were included, mean age 79.3 ± 8.5, male 53.7% (n = 161). 220 pts were received DOAC being naïve (70.7%), while 88 (29.3%) transitioned from vitamin K antagonists. Mean follow-up was 1.5 years from first DOAC prescription. Most prescribed DOACs was rivaroxaban (n = 107), followed by apixaban (n = 82), edoxaban (n = 59) and dabigatran (n = 52). No significant differences in age, gender, CHA2DS2VASc or HASBLED score was detected. Throughout follow-up, 61 patients (20.3%) needed changes in anticoagulation regimen. 24 patients changed DOAC dosage (8%), while 40 patients changed anticoagulants (13.3%), 39 switched from DOAC to another DOAC, 1 from DOAC to warfarin. Annual DOAC-to-DOAC switching rate was 15.0% (95%CI 10.8-20.3). Prevalence of switch varied across DOACs: 28.8% of pts taking dabigatran switched vs 11.0%, 10.2% and 9.3% of those taking apixaban, edoxaban and rivaroxaban respectively (p < 0.05). Apixaban was the most commonly preferred DOAC after switch, with 43% of pts receiving it after crossover.  Causes of switch included minor bleeding (n = 15), major bleeding (n = 3), non-cardiovascular adverse events (n = 14), drug interaction or surgery (n = 4), renal function worsening (n = 2) and low compliance (n = 1). Comparative risk analysis revealed that prescription of dabigatran was associated with a 3-fold increase in risk of switching treatment (OR 3.59, 95%CI 2.09-6.19) compared to other DOACs. Apixaban, rivaroxaban and edoxaban seemed to have similar profile in terms of long-term adherence to treatment . Cox regression analysis, taking into account age, weight, CHA2DS2VASc and HASBLED scores, revealed significant differences in temporal distribution of crossover, with pts in dabigatran more likely to change treatment (HR 2.5, p < 0.05). After switching, 34 out of 39 pts remained free from cardiovascular events and non-cardiovascular adverse events. One pt had minor bleeding, only 1 had major (non-fatal) bleeding, and none reported compliance issues. Non-cardiovascular adverse events completely resolved after switch . Conclusion: Minor bleeding and non cardiovascular adverse events are the most common causes of switch, which has a rate as high as 15% year. Crossover between DOACs seems safe, and might therefore be considered after minor bleeding and non-cardiovascular adverse events